Genetic targeting of NRXN2 in mice unveils role in excitatory cortical synapse function and social behaviors - Born, Gesche; Grayton, Hannah M.; Langhorst, Hanna; Dudanova, Irina; Rohlmann, Astrid; Woodward, Benjamin W.; Collier, David A.; Fernandes, Cathy; Missler, Markus (Frontiers in Synaptic Neuroscience, 2015)
Human genetics has identified rare copy number variations and deleterious mutations for all neurexin genes (NRXN1-3) in patients with neurodevelopmental diseases, and electrophysiological recordings in animal brains have shown that Nrxns are important for synaptic transmission. While several mouse models for Nrxn1α inactivation have previously been studied for behavioral changes, very little information is available for other variants. Here, we validate that mice lacking Nrxn2α exhibit behavioral abnormalities, characterized by social interaction deficits and increased anxiety-like behavior, which partially overlap, partially differ from Nrxn1α mutant behaviors. Using patch-clamp recordings in Nrxn2α knockout brains, we observe reduced spontaneous transmitter release at excitatory synapses in the neocortex. We also analyse at this cellular level a novel NRXN2 mouse model that carries a combined deletion of Nrxn2α and Nrxn2β. Electrophysiological analysis of this Nrxn2-mutant mouse shows surprisingly similar defects of excitatory release to Nrxn2α, indicating that the β-variant of Nrxn2 has no strong function in basic transmission at these synapses. Inhibitory transmission as well as synapse densities and ultrastructure remain unchanged in the neocortex of both models. Furthermore, at Nrxn2α and Nrxn2-mutant excitatory synapses we find an altered facilitation and N-methyl-D-aspartate receptor (NMDAR) function because NMDAR-dependent decay time and NMDAR-mediated responses are reduced. As Nrxn can indirectly be linked to NMDAR via neuroligin and PSD-95, the trans-synaptic nature of this complex may help to explain occurrence of presynaptic and postsynaptic effects. Since excitatory/inhibitory imbalances and impairment of NMDAR function are alledged to have a role in autism and schizophrenia, our results support the idea of a related pathomechanism in these disorders.